Textile design as a resignification tool for post-COVID-19 antimicrobial tissues - Godoy, Sarah de; Sogabe, Milton (DAT Journal, 2021)
This article analyzes the improvement of functional, aesthetic and ergonomic aspects in the design of clothing textiles with the use of nanotechnology. To this end, we consider the phenomena that generate resignifications for the design of textiles for the manufacture of articles for clothing, considering the world after COVID-19. We User a qualitative and bibliographic method, associated with philosophical questions of design, based on conceptual reflections on the universe of design and what are the dialogues in this field with the production of antimicrobial fabrics for clothing in the post-COVID-19 world.